Comparative Profiling of miRNAs and Target Gene Identification in Distant-Grafting between Tomato and Lycium (Goji Berry) - Khaldun, A. B. M.; Huang, Wenjun; Lv, Haiyan; Liao, Sihong; Zeng, Shaohua; Wang, Ying (Frontiers in Plant Science, 2016)
Local translocation of small RNAs between cells is proved. Long distance translocation between rootstock and scion is also well documented in the homo-grafting system, but the process in distant-grafting is widely unexplored where rootstock and scion belonging to different genera. Micro RNAs are a class of small, endogenous, noncoding, gene silencing RNAs that regulate target genes of a wide range of important biological pathways in plants. In this study, tomato was grafted onto goji (Lycium chinense Mill.) to reveal the insight of miRNAs regulation and expression patterns within a distant-grafting system. Goji is an important traditional Chinese medicinal plant with enriched phytochemicals. Illumina sequencing technology has identified 68 evolutionary known miRNAs of 37 miRNA families. Moreover, 168 putative novel miRNAs were also identified. Compared with control tomato, 43 (11 known and 32 novels) and 163 (33 known and 130 novels) miRNAs were expressed significantly different in shoot and fruit of grafted tomato, respectively. The fruiting stage was identified as the most responsive in the distant-grafting approach and 123 miRNAs were found as up-regulating in the grafted fruit which is remarkably higher compare to the grafted shoot tip (28). Potential targets of differentially expressed miRNAs were found to be involved in diverse metabolic and regulatory pathways. ADP binding activities, molybdopterin synthase complex and RNA helicase activity were found as enriched terms in GO (Gene Ontology) analysis. Additionally, ‘metabolic pathways’ was revealed as the most significant pathway in KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis. The information of the small RNA transcriptomes that are obtained from this study might be the first miRNAs elucidation for a distant-grafting system, particularly between goji and tomato. The results from this study will provide the insights into the molecular aspects of miRNA-mediated regulation in the medicinal plant goji, and in grafted tomato. Noteworthy, it would provide a basis how miRNA signals could exchange between rootstock and scion, and the relevance to diverse biological processes.